Villages photography record: Topics of speech and reception about the local roots - Meire Soares Raslan, Eliane (Guará Journal, 2017)
We are looking for the Muquifu Museum - Museum of Quilombos anda Favelas Urbanas, from Vila Estrela in te agglomerate Morro do Papagaio in Belo Horizonte, to treat the visual reception of the local roots of this community. Muquifu is a museum that appears with the motivation to register the real and (in) visible community, before all the residents were removed from the cluster based on photos, illustrations / paintings and objects produced and donated by people who lived or lived in these villages. It remains a combination of people being recorded from photos and illustrations, it is the real becoming printed, it is the immaterial materializing, they are images gaining a greater dimension through aesthetics and dialogue. These effects of sense are caused by the images (photo, illustration and objects), where time and space will unleash the community. We propose to analyze the adequacy of Muquifu images in the pretension of indentifying roots, cultural manifestations and their importance as history through Discourse Analyses (AD) with Eliseo Verón.
Keywords: Discourse analysis; Eliseo Verón; Photos and illustrations; Villages and reception